Comparative Education antara MTS As-Shiddiqi dengan SMP Katolik di Kabupaten Pamekasan - Wardi, Moh; Supandi, Supandi (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2018)
Building harmonious and peaceful interaction between communities of different religions, is necessary to change the theological paradigm; that is passive, textual, and exclusive, leading towards the theology of inclusive, mutual respect, mutual recognition of existence, thinking and being positive among others. The paradigm of plural education in the future is democratic education, this can only be realized in a democratic society, nation and country. By providing the opportunities for the implementation of harmony and peace. The author describes about the Comparison of Islamic Education with Non-Islam (comparative study in Madrasah Tsanawiyah As-Shiddiqi and Catholic Junior High Schools (SMP) in Pamekasan Regency). The different point of these two educational institutions is the allocation of lesson hour (JTM). In Islamic Education is 2 hours a week in each religious material including Fiqh, Al-Quran, Aqidah and SKI subjects. Whereas in Catholic education is only given about 2 lessons, and the other is the same as other general education. For educational institutions that are speciï¬ed into Uskupan or Romo, the applied curriculum is a matter of theology, such as seminaries starting from senior high school until university